Immediate interviewing increases children's suggestibility in the short term, but not in the long term. (3rd August 2018) - Otgaar, Henry; Chan, Jason C. K.; Calado, Bruna; La Rooy, David
Abstract : Purpose: Children sometimes receive misinformation after being formally interviewed about their experiences in cases of suspected abuse. Following decades of research, many guidelines have been produced for interviewers so they can obtain reliable statements in children, like, for example, the NICHD protocol. One might expect that completing an early interview following research‐based guidelines might guard against the incorporation of misinformation encountered later. The goal of the current experiments was to examine whether following research‐based guidelines such as the NICHD protocol might protect child witnesses against follow‐up 'misinformation' or make them more vulnerable to misinformation. This increased vulnerability to misinformation has been referred to as retrieval‐enhanced suggestibility . Methods: In two experiments, children viewed a video and half of them were interviewed using the NICHD protocol, while the other half were not interviewed. The children received misinformation and a final memory test either immediately after being interviewed (Experiment 1) or 1 week later (Experiment 2). Results: Retrieval‐enhanced suggestibility was observed when misinformation was presented immediately but not when it was provided after 1 week. Conclusions: The current experiments indicate that a well‐established interview protocol can, under some circumstances, amplify levels of suggestibility in children.